2009
DOI: 10.1128/jvi.02392-08
|View full text |Cite
|
Sign up to set email alerts
|

Latent Species C Adenoviruses in Human Tonsil Tissues

Abstract: Although species C human adenoviruses establish persistent infections, the molecular details of this lifestyle remain poorly understood. We previously reported that adenovirus DNA is found in human mucosal T lymphocytes in a noninfectious form (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
202
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(226 citation statements)
references
References 60 publications
20
202
2
1
Order By: Relevance
“…We found that the vast majority of adenovirus DNA in tonsil and adenoids is quiescent and preferentially localized in the Tlymphocyte population (12). More recently, we reported that while only a small minority of samples from tonsil donors contain replicating virus (Ͻ15%), most tissue samples (85%) could be stimulated in vitro to activate virus gene expression and replication (13). Together, these findings reveal infection by species C adenoviruses as a two-step process of acute replication in epithelial cells of the nasopharyngeal mucosa, followed by latent infection of lymphocytes in mucosa-associated lymphoid tissues.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…We found that the vast majority of adenovirus DNA in tonsil and adenoids is quiescent and preferentially localized in the Tlymphocyte population (12). More recently, we reported that while only a small minority of samples from tonsil donors contain replicating virus (Ͻ15%), most tissue samples (85%) could be stimulated in vitro to activate virus gene expression and replication (13). Together, these findings reveal infection by species C adenoviruses as a two-step process of acute replication in epithelial cells of the nasopharyngeal mucosa, followed by latent infection of lymphocytes in mucosa-associated lymphoid tissues.…”
mentioning
confidence: 89%
“…In naturally infected tonsil lymphocyte populations, the frequency of adenovirus-bearing cells is very low, on the order of 1 cell in 10 4 to 10 5 (13). As an initial step in developing a picture of adenovirus infections in lymphocytes, a number of groups have reported success at infecting human lymphocyte cell lines with species C adenoviruses, and most infections appeared to be nonlytic (5,17,19,20,33), at least over the short term.…”
mentioning
confidence: 99%
“…More than 50 different Ad serotypes have been distinguished, which are classified in six different species (2). In a considerable proportion of patients, Ads persist for a variable length of time after primary infection and may become latent (3,4), with members of species C (e.g., Ad2 or Ad5) being most often detected (3). Their successful propagation in vivo is facilitated by multiple strategies to evade the host immune response (1,5,6).…”
mentioning
confidence: 99%
“…Interpretation of HAdV detection in pediatric respiratory samples can be difficult, as HAdV (especially species C) is known to establish persistence, with low levels of detection in tonsils and adenoids for years (5,6). Therefore, detection of HAdV in the NP by PCR does not necessarily reflect acute disease in children (10).…”
Section: Filmarray Rp V17 For Detection Of Hadv In Childrenmentioning
confidence: 99%